Tropes and Rhetorical Figures in Simultaneous Interpreting of Presidential Speeches - Pelenytė, Guoda; Grigaliūnienė, Jonė (Vertimo studijos, 2021)
Since one of the distinctive features of presidential speeches is the use of tropes and rhetorical figures, which are employed to achieve a persuasive effect, this study aimed to find out if tropes and rhetorical figures are retained in simultaneous interpretation from English into Lithuanian and whether the omission of them in the interpretation diminishes the rhetorical effect of the speech. The research found that out of 500 tropes and rhetorical figures observed in original speeches more than a half are absent in interpretation. Based on a closer analysis of examples, it was concluded that tropes and rhetorical figures tend to cause problems for interpreters and that the omission of tropes and rhetorical figures results in a diminished rhetorical effect in the target language.
Keywords: presidential rhetoric; tropes; rhetorical figures; simultaneous interpreting